2016
DOI: 10.4102/phcfm.v8i2.945
|View full text |Cite
|
Sign up to set email alerts
|

Views of teenagers on termination of pregnancy at Muyexe high school in Mopani District, Limpopo Province, South Africa

Abstract: BackgroundTeenage pregnancy is a global social health concern especially because of the HIV and AIDS pandemic, sexually transmitted infections, high rate of termination of pregnancy (TOP), adolescents’ parenthood and decreased level of contraceptives.AimTo explore the views of teenagers on the TOP at Muyexe high school in a rural village of Mopani District, Limpopo Province.SettingMuyexe high school in a rural village of Mopani District, Limpopo Province, in South Africa.MethodologyA qualitative method using e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(56 citation statements)
references
References 7 publications
2
43
0
2
Order By: Relevance
“…Some of the adolescent women in this study narrated how they tried to abort the pregnancy to avoid any embarrassment. This finding is consistent with others (Atuyambe et al, 2005;Ramakuela, Lebese, Maputle, & Mulaudzi, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…Some of the adolescent women in this study narrated how they tried to abort the pregnancy to avoid any embarrassment. This finding is consistent with others (Atuyambe et al, 2005;Ramakuela, Lebese, Maputle, & Mulaudzi, 2016).…”
Section: Discussionsupporting
confidence: 94%
“…rape or incest); the South African cohort also reported fears of physical trauma due to childbirth as a reason for abortion. 30,31 Baba et al, in Japan, also showed that girls 10-14 were more likely to experience pregnancy due to rape or incest than older adolescents. 32 In Nigeria, adolescents who had undergone abortion were significantly more likely to have experienced transactional or forced sex.…”
Section: Abortion Knowledge and Attitudesmentioning
confidence: 99%
“…28,34 Dahlback et al, in Zambia, and Ramakeula et al, in South Africa, confirmed that girls consider pregnancy shameful and stigmatising for themselves and their families, often leading them to undergo an unsafe abortion. 29,30 Poverty and fear for the girls' maternal health were also important factors in abortionseeking in a number of contexts including Nigeria and Bangladesh. 19,33 Timing of abortion and post-abortion care Once the decision has been made to terminate a pregnancy, adolescents are more likely to delay the timing of abortion and post-abortion care.…”
Section: Abortion Knowledge and Attitudesmentioning
confidence: 99%
“…It seems reasonable to suppose that for children and adolescents, as well as for their legal representatives, it may be less tolerable to keep gestation resulting from incest, leading to lesser giving up of abortion. This lesser tolerance may include social and cultural factors, such as the findings of the Ramakuela et al 26 study, concluding that incest was decisive for the option to abort among South Africa adolescents, as some of the girls believed that to keep gestation would bring curse and break to the family.…”
Section: Sexual and Gender Violencementioning
confidence: 99%